Landscape genetics identified conservation priority areas for blue sheep (Pseudois nayaur) in the Indian Trans-Himalayan Region - Stanzin Dolker; Gul Jabin; Sujeet Kumar Singh; Bheem Dutt Joshi; Vinaya Kumar Singh; Supriyo Dalui; Kailash Chandra; Lalit Kumar Sharma; Mukesh Thakur (Scientific Reports, 2023)
Abstract The trans-Himalayan region of India, although have xeric features, still supports a unique assemblage of biodiversity, including some of the charismatic and endemic species. In the present study, we studied blue sheep (Pseudois nayaur) across the distribution range in the Western trans Himalayas of India and found about 18,775 km2 area suitable for blue sheep. The explicit Bayesian based spatial and non-spatial population structure analysis assigned blue sheep into two genetic populations, i.e., Ladakh and Lahaul-Spiti. We found relatively high genetic divergence in blue sheep which is also supported by the low current flow in Circuitscape model. With the multiple evidences, we explain landscape resistance facilitated by the landscape heterogeneity, and large patches of unsuitable habitats forced population divergence and poor functional connectivity. We found that blue sheep population has been demographically stable in the past, but showed a slight decline within the last few decades. This study is the first range-wide attempt to exhibit landscape features in shaping the spatial distribution, genetic structure and demography patterns of blue sheep in Western Himalayas, and will be of use in the conservation and management planning of blue sheep.